A rare case report of teen‐onset pica in a female patient with a clinical high risk for psychosis. Issue 7 (23rd August 2021) - Fekih‐Romdhane, Feten; Cheour, Majda
Abstract: Aim: We aimed to further elucidate the under‐researched, underdiagnosed and misunderstood comorbid pica in the context of psychosis. Method: We report a case of teen‐onset plastophagia in an antipsychotic‐naïve girl at ultra‐high risk (UHR) for psychosis. Results: HA is a 17‐year‐old unmarried girl who had a history of good premorbid functioning, no personal psychiatric history and an uncle with schizophrenia. She was referred to our psychiatry department with the complaint of having the habit of eating plastic for about 2 years. A thorough clinical history revealed that she developed, since more than a year, difficulty in school and interpersonal functioning. After clinical evaluation, a diagnosis of UHR with major depressive disorder, iron deficiency anaemia and pica was made. Conclusion: We draw attention to the possibility of an overlap between the pathogenesis of pica and psychosis, and we highlight the importance of early diagnosis and management of both pica and UHR since they can lead to serious medical and mental consequences.